Walking in a self-selected enjoyable colored environment: exploring gender-specific effects and dynamics of affects, perceived exertion, heart rate, and preferred walking speed - Hassanein, Youmna Elsayed; Briki, Walid; Majed, Lina (Frontiers in Psychology, 2025)
AimExisting literature suggests that exposure to colored environments can influence psychological, physiological, and behavioral responses. This study examined the effects of experiencing a self-selected enjoyable colored environment, compared to a neutral one, on psychological and physiological responses, as well as preferred walking speed during a 20-min treadmill walk.MethodsEighty participants (40 females) were randomly assigned to either an experimental group (preferred colored environment) or a control group (neutral gray environment). Data were collected at five regular intervals during the treadmill walk.ResultsParticipants walked significantly slower in the colored environment compared to the neutral one, with this effect more pronounced in females, who significantly reduced their walking speed, while males remained unaffected. The walking task generally decreased depression and confusion levels; females showed a stronger reduction in depression, while males exhibited no significant change. During the task, females revealed significantly higher levels of perceived exertion and heart rate compared to males. A dynamic pattern emerged over time, with increases in perceived exertion, arousal, heart rate, and walking speed, while pleasure levels remained stable.ConclusionsThe findings suggest that females are more responsive—psychologically, physiologically, and behaviorally—to both the preferred colored environment and the walking task, demonstrating a greater tendency to derive wellbeing benefits from subtle stimuli. Furthermore, the observed dynamic pattern suggests the view that self-paced walking is intrinsically governed by a pleasure-driven dynamic. These insights offer valuable implications for designing tailored interventions and strategies to promote physical activity through walking. Future research should further explore the role of color preference perception and self-paced walking in enhancing wellbeing, particularly within exercise and rehabilitation contexts.